Faults and Non‐Double‐Couple Components for Induced Earthquakes. Issue 17 (14th September 2018) - Wang, Ruijia; Gu, Yu Jeffrey; Schultz, Ryan; Chen, Yunfeng
Abstract: Focal mechanisms of induced earthquakes reflect anthropogenic contributions to preexisting geological features and fault slippages. In this paper, we examine fault‐related (double‐couple (DC)) and possibly fluid‐related (non‐double‐couple (non‐DC)) mechanisms of induced earthquakes ( M 2–6) at regional scales. We systematically compare well‐resolved focal mechanisms of 33 events in the Western Canada Sedimentary Basin, among which 12 were induced by hydraulic fracturing and one by secondary recovery. Most of the seismicity is dominated by strike‐slip/thrust faulting regimes, whereas limited (but consistent) non‐DC components are obtained from injection‐induced seismicity in central Alberta. We interpret the persistent compensated‐linear‐vector‐dipole components ( M 2.1–3.8) as reflecting fracture growth and/or noncoplanar faults slippages during hydraulic‐fracturing stimulations. We further expand the moment tensor decomposition analysis to four representative classes of induced seismicity globally and find that the overall contribution of non‐DC components is comparable between induced and tectonic earthquakes. Plain Language Summary: Source mechanism of induced (man‐made) earthquakes reflects human contributions to the fault slippages. We examine fault‐related and possibly fluid‐related components of the earthquake sources from western Canada and find evidence for fracture growth and/or nonplanar fault slippages during hydraulic‐fracturing stimulations. We also systematically compare the well‐resolved focal mechanisms of 79 earthquakes (induced by different reasons) with 24 natural ones. The results of our statistical analysis suggest that induced and natural earthquakes are similar in view of source mechanism. Key Points: Recent M ~4 induced earthquakes in western Canada can be categorized into strike‐slip and reverse‐faulting regimes, similar to tectonic ones Consistent CLVD components reflect fault/fracture growth or en echelon fault slipping Induced earthquakes exhibit indistinguishable amounts of non‐DC components from tectonic earthquakes